Implementation of Mediation Effort For Settlement At The Class Ia Religious Court In Jayapura - Ingratubun, Husni; Ingratubun, Fitri (Faculty of Law, Universitas Pattimura, 2023)
Introduction: In handling cases, mediation is the most important series in the overall handling of judicial cases.Purposes of the Research: This study uses field research, by looking at phenomena related to procedures for mediating in resolving family conflicts in the Religious Courts. Sociologically -idealistically , mediation can help conflicting parties to get justice and benefit through peaceful means , but empirically-realistically, mediation procedures to resolve family conflicts in the Class IA Court in Jayapura which lead to decisions so that the role of the mediator cannot function maximally.Methods of the Research: This study aims to identify, study and analyze the implementation of mediation using a legal perspective and PERMA Number 1 of 2016 concerning Mediation Procedures in the District Court, and to find out, examine and analyze the effectiveness of the implementation of PERMA RI No. 1 of 2016 in the District Court in Jayapura.Results of the Research: The results of this study can be concluded that the implementation of mediation in a positive legal and legal perspective in the Religious Courts in Jayapura, in its implementation as it should and can resolve family conflicts, can be judged to be less successful, due to family conflicts to the forum as a large mediation, although the process of This can result in a complete resolution of the problem to the fullest, in fact the troubled parties still do not accept a reason for making peace. When the family parties are involved in a conflict, it must be immediately reconciled peacefully based on the existing legal provisions.